Interprofessional Learning Development In Indonesia Health Study Program - Fairuz, Fairuz; Shafira, Nyimas Natasha Ayu; Aryanty, Nindya; Raudhoh, Siti; De Jonge, Laury P.J.W.M. (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Interprofessional education (IPE) is a joint learning process between two or more students from the health profession to develop collaboration skills and improve the quality of health services. With IPE, students develop a deeper understanding of various health professions’ roles and responsibilities, enhancing their ability to communicate and collaborate effectively. This study aims to develop IPE learning involving five health professions at the Faculty of Medicine and Health Sciences Universitas Jambi. Methods: This study uses a research and development design. This study utilized a qualitative approach, specifically through Focus Group Discussions (FGDs) at the research and information gathering (define) stage. A total of ten lecturers and five heads of study programs from medical, nursing, pharmacies, psychology, and public health programs were involved in this study. Results: Three themes were derived from the results: Curriculum, Faculty Development, and Institutional Support. Community-based IPE allows students from various health study programs at FKIK UNJA to be involved in these activities. To ensure effective implementation of IPE learning, it is crucial to conduct training for faculty facilitators and field instructors related to IPE learning and to form a team responsible for developing, delivering, and managing the IPE program. Institutional support for interprofessional education (IPE), namely facilities, infrastructure, and a partnership with primary health centers, is critical for implementing and sustaining community-based IPE. Conclusion: The IPE learning that will be implemented at FKIK UNJA is community-based IPE. Three crucial elements must be prepared to implement IPE: curriculum, faculty development, and institutional support. Keywords: Interprofessional Education; Community-Based Setting